2012
DOI: 10.5489/cuaj.163
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary malignancy presenting as an ocular metastasis: A case report and review of the literature

Abstract: E67Case report Genitourinary malignancy presenting as an ocular metastasis: A case report and review of the literature Cite as: Can Urol Assoc J 2012;6(2):e67-71. http://dx.doi.org/10.5489/cuaj.10174 AbstractMetastases to the eye or orbit as the initial presentation of genitourinary malignancy are unusual and can be a diagnostic challenge. We report an 81-year-old man who presented with pain and proptosis in an eye that had been blind for 50 years. Radiologic investigations identified a mass involving the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Bone metastases are usually predominantly osteoblastic (95%). 7,8 The detection of orbital lesions starting from a solid cancer is still considered a challenging task due to their wide variety of anatomical and clinical features. Indeed, orbital metastases may be intraconal or extraconal and may present different patterns, from a focal lesion to a massive infiltrative one.…”
Section: Resultsmentioning
confidence: 99%
“…Bone metastases are usually predominantly osteoblastic (95%). 7,8 The detection of orbital lesions starting from a solid cancer is still considered a challenging task due to their wide variety of anatomical and clinical features. Indeed, orbital metastases may be intraconal or extraconal and may present different patterns, from a focal lesion to a massive infiltrative one.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we present the largest case series so far of patients with rare optic canal metastases due to PCa. Our study identified 45 cases of metastatic PCa with optic canal involvement reported in the literature [ 4 - 30 ]. We engage in an analysis of their clinical characteristics, notable histology, and treatment modalities.…”
Section: Introductionmentioning
confidence: 99%